(untitled) (Texas Journal of Medical Science, 2023)
Sanitary protection of water bodies means a set of measures (legislative, organizational, economic, planning, scientific, technological, sanitary-technical) that ensure such a state of water resources that makes it possible to use them for household and drinking water supply of the population, bathing, physical culture, therapeutic and recreational purposes, and also preserves important water bodies importance in the formation of the microclimate of populated areas and their landscape and architectural expressiveness. In other words, it is the protection of water bodies from sources of pollution.